Can wild lentil genotypes help improve water use and transpiration efficiency in cultivated lentil?. Issue 5 (6th March 2018) - Gorim, Linda Yuya; Vandenberg, Albert
Abstract: Climate change forecasts point to increased frequency of droughts which may affect plant growth. For protein crops such as lentil, genetic improvement of both water use and drought tolerance is necessary. Wild lentil species are known to have evolved in drought prone areas and can be introgressed into cultivated lentil, making them candidates for the evaluation of high transpiration efficiency (TE) and drought tolerance. We assessed TE, water use and drought tolerance at the plant level for five wild lentil species and in cultivated lentil. Under fully watered and moderate drought conditions, wild lentil genotypes consumed significantly less water to fix similar or more dry matter compared with their cultivated counterparts. Under severe drought conditions, the wild lentil genotype L. ervoides IG 72815 had significantly higher TE compared with L. culinaris Eston. Lens ervoides L-01-827A, had significantly higher yield compared with all other species in the presence or absence of drought and showed significantly higher ( α = 5%) TE under moderate drought. Drought susceptibility index was identified as a tool to identify drought-tolerant lentil genotypes grown under severe drought. The numerous small seeds of wild lentil made it difficult to estimate drought indices that are weight based and require formulae that incorporate seed numbers.